AB271. SOH26AB_0103. Anaesthetic management of a patient with myofibrillar myopathy undergoing carotid endarterectomy: a case report - Lonappan, Aneesa Mangalam; Feeley, Tara (Mesentery and Peritoneum, 2026)
Myofibrillar myopathies are rare neuromuscular disorders associated with progressive muscle weakness, respiratory compromise, and potential cardiac involvement. These conditions carry significant anaesthetic risk, particularly in the context of major vascular surgery, due to susceptibility to rhabdomyolysis, arrhythmias, and malignant hyperthermia-like reactions when exposed to volatile anaesthetic agents or depolarising neuromuscular blocking agents.